Social Responsibility & Ethics in Marketing during crisis - Naumovska, Ljupka; Jovevski, Dimitar; Brockova, Katarina (The International Virtual Conference on Management and Economics, 2020)
The ongoing COVID19 crisis is affecting the globe on three levels: health crisis, economic crisis and social panic. Consequently, there are firm predictions for a global recession unfolding in the upcoming months / years. On the other hand, having very limited outlets for communications, the Governments all over the world have undertaken set of measures, communication styles and crisis toolkits that are being criticized by the academic, NGO and general audience. This paper is based on published academic research studies for past and currents crisis, as well as current media data and cases emerging in the course with the novel coronavirus situation, unfolding many new forms and requests for crisis communication. While, the complexity of this crisis is obvious, the urge to learn new lessons and frame new communication models emerges. This paper captures events and offers conceptual framework in the context of the novel coronavirus crisis communication, as events and conclusions are unfolding currently, and invites future research, during and after the crisis to complete the findings.
Keywords: crisis communication, marketing, ethics.